Pemberdayaan UMKM Mebel Oleh Dinas Koperasi dan Usaha Mikro Kota Pasuruan Tahun 2019-2022 - Fadhilah, Maharani Ulya; Prathama, Ananta (Populis : Jurnal Sosial dan Humaniora, 2023)
Empowering MSMEs has become an obligation for local governments to encourage MSMEs to have economic independence. However, in practice it is known that MSMEs actors in Pasuruan City, especially furniture MSMEs, still do not have sufficient skills and knowledge in managing a business and the low participation in empowerment activities carried out by local governments so that this has implications for declining MSMEs furniture income. This research aims to analyze the empowerment of furniture MSMEs by the Department of Cooperatives and Micro Enterprises of Pasuruan City throughout 2019-2022. This research method usesl la qualitative descriptive lapproach. lData obtained lthrough lobservation, llinterviews, land ldocumentation. From lthe lresults lof lthe lstudy lit was found lthat lthe empowerment that had been carried out lby lthe lOffice of lCooperatives land lMicro lEnterprises in lPasuruan lCity had succeeded in empowering Furniture MSMEs because it was supported by the Kurma lprogram lwhich lresulted lin lan lincrease lin lthe lnumber lof MSMEs gurniture businesses. Apart from that, there is also an easy program for granting business permits with the SIUP pick-up program. However, in the form of empowering education and training as well as product marketing, more comprehensive and massive efforts need to be made.Pemberdayaan pada UMKM telah menjadi suatu kewajiban bagi pemerintah daerah untuk mendorong pelaku UMKM memiliki kemandirian secara ekonomi. Akan tetapi, dalam praktiknya diketahui para pelaku UMKM di Kota Pasuruan khususnya UMKM mebel masih belum memiliki kemampuan dan pengetahuan yang cukup dalam mengelola usaha serta rendahnya partisipasi dalam kegiatan pemberdayaan yang dilakukan oleh pemerintah daerah sehingga berimplikasi pada pendapatan UMKM mebel yang menurun. Penelitianl inil bertujuanl untukl menganalisis pemberdayaanl UMKMl mebel olehl Dinas lKoperasi ldan Usaha Mikro Kota Pasuruan sepanjang tahun 2019-2022. Metodel penelitianl inil menggunakanl pendekatanl deskriptif lkualitatif. Datal diperolehl melaluil lobservasi, lwawancara, ldan ldokumentasi. Dari lhasil lpenelitian didapat lbahwa pemberdayaan yang telah dilakukan lDinas lKoperasi ldan lUsaha lMikro Kota Pasuruan ltelah berhasil memberdayakan lpara lpelaku lUMKM lmebel karena didukung oleh program Kurma yang menghasilkan peningkatan jumlah usaha UMKM mebel. Selain itu juga adanya program pemberian izin usaha yang mudah dengan program jemput bola SIUP. Akan tetapi, pada bentuk pemberdayaan pendidikan dan pelatihan serta pemasaran produk perlu dilakukan upaya yang lebih komprehensif dan masif.